Discharge Criteria for the Late Preterm Infant: A Review of the Literature. (October 2017) - Quinn, Jenny M.; Sparks, Marteen; Gephart, Sheila M.
Abstract : Background: Standardized late preterm infant (LPI) discharge criteria ensure best practice and help guide the neonatal provider to determine the appropriate level of care following birth. However, the location can vary from the well newborn setting to the neonatal intensive care unit (NICU). Purpose: The purpose of this review is to examine differences in LPI discharge criteria between the well newborn setting and the NICU by answering the clinical questions, "What are the recommended discharge criteria for the LPI and do they differ if admitted to the well newborn setting versus the NICU?" Search Strategy: Databases searched include CINAHL, TRIP, PubMed, and the Cochrane Library. Focusing first on the highest level of evidence, position statements, policy statements, and clinical practice guidelines were reviewed, followed by original research. Results: There were few differences shown between settings. Discharge criteria included physiological stability and completed screenings for hearing loss, hyperbilirubinemia, car seat safety, hypoglycemia, critical congenital heart disease, and sepsis. Parent education is provided on umbilical cord care, feeding, elimination, and weight gain norms. Recommended maternal assessment included screenings for depression, drug use, safe home environment, and presence of social support. In general, research supported protecting the mother-infant dyad. Implications for Practice and Research: Developing a standardized approach for discharge criteria for LPIs may improve outcomes and reduce maternal stress. Research is needed to compare health and cost outcomes between settings. Video Abstract available athttp://links.lww.com/ANC/A29 . Abstract : Supplemental Digital Content is Available in the Text.